2020
DOI: 10.1038/s41598-020-75855-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding complex dynamics of behavioral, neurochemical and transcriptomic changes induced by prolonged chronic unpredictable stress in zebrafish

Abstract: Stress-related neuropsychiatric disorders are widespread, debilitating and often treatment-resistant illnesses that represent an urgent unmet biomedical problem. Animal models of these disorders are widely used to study stress pathogenesis. A more recent and historically less utilized model organism, the zebrafish (Danio rerio), is a valuable tool in stress neuroscience research. Utilizing the 5-week chronic unpredictable stress (CUS) model, here we examined brain transcriptomic profiles and complex dynamic be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 155 publications
(192 reference statements)
2
46
0
Order By: Relevance
“…7A). These results replicate and reinforce previous studies showing that UCS induces anxiety-like behavior in zebrafish (Chakravarty et al, 2013; Demin et al, 2020; Marcon et al, 2019, 2018a, 2016; Mocelin et al, 2019; O’Daniel and Petrunich-Rutherford, 2020; Piato et al, 2011; Reddy et al, 2021; Song et al, 2018). Both CUR and MC were unable to block these alterations.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…7A). These results replicate and reinforce previous studies showing that UCS induces anxiety-like behavior in zebrafish (Chakravarty et al, 2013; Demin et al, 2020; Marcon et al, 2019, 2018a, 2016; Mocelin et al, 2019; O’Daniel and Petrunich-Rutherford, 2020; Piato et al, 2011; Reddy et al, 2021; Song et al, 2018). Both CUR and MC were unable to block these alterations.…”
Section: Resultssupporting
confidence: 92%
“…The unpredictable chronic stress induces several behavioral and neurochemical characteristics that resemble those observed in patients with anxiety and/or mood disorders (Chattarji et al, 2015; Willner, 2017, 2005). Antidepressants (Demin et al, 2020; Marcon et al, 2016; Reddy et al, 2021; Song et al, 2018), anxiolytics (Marcon et al, 2016), antioxidant (Marcon et al, 2019; Mocelin et al, 2019), ketamine (Reddy et al, 2021) and prazosin (O’Daniel and Petrunich-Rutherford, 2020) showed protective effects in this model.…”
Section: Resultsmentioning
confidence: 84%
“…Comparing our present rat PCUS results with mouse data in a different, social defeat-based chronic stress model, 153 , we note that both stressors reduce hippocampal expression of Dedicator Of Cytokinesis 10 ( Dock10 ), a poorly studied immune gene 154 . Cardiac muscle troponin T ( Tnnt2 ) orthologues ( Tnnt2 and tnnt2a ), parts of the troponin complex, were both upregulated in PCUS rats and in zebrafish subjected to 5-week PCUS 74 . However, novel data mining tools are needed to target species-specific and cross-species data, also aiming to identify evolutionarily conserved core aspects that may be used to better compare and interpret animal data.…”
Section: Discussionmentioning
confidence: 99%
“…Brain samples for transcriptomic analyses were collected without pooling (1 brain per sample) one day after the last behavioral test, between 9:00 and 19.00. The 1-day interval was used here to minimize concomitant immediate genomic effects of behavioral testing and/or handling 74 . Rats (n=3) for RNA-sequencing analysis were chosen from the groups using a random number generator (https://www.random.org/).…”
Section: Methodsmentioning
confidence: 99%
“…Since brain monoaminergic systems play a key role in NBOMe CNS effects 3137 , here we studied changes in zebrafish whole-brain concentrations of norepinephrine (NE), serotonin (5-HT), dopamine (DA) and their metabolites 5-hydroxyindoleacetic acid (5-HIAA), 3,4-dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA) using the high-performance liquid chromatography (HPLC), similarly to 73, 74, 77, 96, 102, 103 . As in the NTT and ZTI studies, fish (n=7-10) were pre-exposed to 20 mg/L of 24H-NBF, 34H-NBOMe, 34H-NBF, 34H-NBCl, 34H-NBBr, 34H-NBOMe, or to 10 mg/L 24H-NBBr, 24H-NBOMe(F) or drug-free water, in the 0.5L beaker for 20 min.…”
Section: Methodsmentioning
confidence: 99%